2012
DOI: 10.1371/journal.pone.0041242
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role for PAD2 in Gene Regulation in Breast Cancer Cells

Abstract: The peptidylarginine deiminase (PAD) family of enzymes post-translationally convert positively charged arginine residues in substrate proteins to the neutral, non-standard residue citrulline. PAD family members 1, 2, 3, and 6 have previously been localized to the cell cytoplasm and, thus, their potential to regulate gene activity has not been described. We recently demonstrated that PAD2 is expressed in the canine mammary gland epithelium and that levels of histone citrullination in this tissue correlate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 34 publications
8
85
0
Order By: Relevance
“…2D). A similar expression of PADI2 was previously described in other epithelial cells from kidney, endometrium, and mammary gland (28).…”
Section: Padi2 Expression Correlates With Enterocytic Differentiationsupporting
confidence: 81%
“…2D). A similar expression of PADI2 was previously described in other epithelial cells from kidney, endometrium, and mammary gland (28).…”
Section: Padi2 Expression Correlates With Enterocytic Differentiationsupporting
confidence: 81%
“…In addition, we found strong nuclear anti-pan-citrulline staining in these lesions (Fig. 2D, inset bottom image), which is in line with our previous studies showing that PAD2-mediated histone deimination regulates gene expression (9,10,14,21). Because the anti-human PAD2 antibody likely cross-reacts with endogenous mouse PAD2, we also stained these tissues with an anti-FLAG antibody to specifically stain the PAD2 fusion protein.…”
Section: Recombinant Pad2 Is Expressed In the Skin And Tumor Tissue Osupporting
confidence: 89%
“…Therefore, while purely speculative, it is possible that the relatively low levels of FLAG-PAD2 that we observed in the skin promotes the expression of a specific ratio of PAD family members that is conducive to inflammation and tumorigenesis, whereas the relatively higher level of FLAG-PAD2 in the mammary gland alters this ratio, leading to reduced inflammatory mediator expression and an absence of neoplastic growth. Regarding the potential mechanisms by which PAD2 overexpression regulates gene activity, we have recently found that PAD2 functions as a transcription factor co-factor and modulates target gene expression via histone deimination at transcription factor-binding sites (9,10,14,21). Therefore, we are currently testing the hypothesis that PAD2 regulates the expression of target genes via similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deregulation of PAD enzymes is involved in cancers and autoimmune disorders [9]. Dr. Coonrod's lab has shown that PAD2 expression is up-regulated in tamoxifen-resistant breast cancer cells [10]. While they predicted that PAD2 might be a driver of breast cancer, unexpectedly, overexpression of PAD2 in mice by the murine mammary tumor virus promoter led to dysplastic tumors in skin cells, but not in mammary glands [11].…”
Section: Introductionmentioning
confidence: 99%